Comparative optical loss analysis of multilayer type-I hyperbolic metamaterials - Kadir Üstün; İbrahim Halil Giden (Engineering Science and Technology, an International Journal)
Hyperbolic metamaterials (HMMs) are finely-structured nanoscale structures, typically consisting of alternating layers of metallic and dielectric materials arranged in a periodic fashion. Thanks to their anisotropic nature, HMMs exhibit extraordinary optical properties, particularly in controlling the behavior of light at the nanoscale such as light bending at extreme angles, negative refraction, subwavelength focusing, tight confinement of light and enhanced surface plasmon polaritons (SPPs). Nevertheless, HMMs may suffer from high intrinsic optical losses, mostly due to the inclusion of the metallic components, degrading their performance and efficiency severely as well as limiting their scalability and widespread adoption.In this study, we offer an unprecedented roadmap for the selection of material pairs while designing Type-I HMM structures. We analyze the dispersion properties, electromagnetic wave scattering from and light propagation through multilayered metamaterials. We make the reflection/optical loss analyses in HMMs and compare the propagation loss of various HMMs found in the literature. We also investigate the figure-of-merit (FOM) parameter that determine the optical loss level of the designed HMMs. We propose a guideline for the material/filling ratio choice of planar multilayered metal-dielectric structure to find the best performing hyperbolic metamaterials for low-loss applications operating at different regions of the electromagnetic spectrum.